MO106: Circulating Neutrophil Count is Associated with Severity of Chronic Kidney Disease. (3rd May 2022) - Carrara, Fabiola; Ruggenenti, Piero; Parvanova, Aneliya; Trillini, Matias; Cugini, Daniela; Stucchi, Nadia; Ferrari, Silvia; Remuzzi, Giuseppe
Abstract: BACKGROUND AND AIMS: Neutrophils (Ns) play a key role in inflammation and tissue injury, in particular in acute renal failure, by releasing a complex of cytotoxic products such as reactive oxygen intermediates, enzymes and microbicidal polypeptides. These effects are prevented or mitigated by Ns depletion [1, 2 ]. Here we investigated the relationships between Ns count and the severity of kidney dysfunction in patients with chronic kidney disease (CKD). METHOD: In this cross-sectional study we evaluated the association between circulating Ns absolute number, CKD stage and measured glomerular filtration rate (mGFR) in 393 patients with renal disease from different causes. CKD stage was established on the basis of mGFR and K/DOQI guidelines [3 ]. The relationships of Ns count and other considered covariates with mGFR were evaluated by uni- and multi-variable linear regression models (Table 1 ). Variables considered in univariable models are listed in Table 1 . Variables included in multivariable models were identified with forward selection. Circulating Ns were measured by Coulter LH 780 Hematology Analyzer (Beckman Coulter, Milan, Italy). The GFR was measured by the iohexol plasma clearance technique, a gold standard for direct GFR measurement [4 ]. P  < .05 was considered as statistically significant. RESULTS: The mean ± SD age and mGFR of the patients were 54.64 ± 13.75 years and 62.75 ± 22.52 mL/min/1.73 m 2  (range: 15.53–131.79 mL/min/1.73 m 2 ), respectively. Most patients had a kidney function in stage 2 and 3a (Figure 1A). The absolute number of Ns averaged 4.32 ± 1.77 × 10 3 µL −1 . Ns counts increased progressively in parallel with increasing CKD stage ( P  < .005, Figure 1A) and were negatively correlated with mGFR ( P  < .001, Figure 1B). At multivariable analysis, mGFR was associated negatively with Ns count and positively with basophils (Bs) count (Table 1 ). CONCLUSION: In patients with CKD higher numbers of Ns and lower numbers of Bs, even within the normal range, were independently associated with more severe renal insufficiency. A major limitation of the study is the cross-sectional design that does not allow to establish a causal relationship between Ns count and severity of kidney dysfunction. These data provide the basis for studies to investigate mechanisms explaining these associations.